Genome-wide positioning of bivalent mononucleosomes. Issue 1 (December 2016) - Sen, Subhojit; Block, Kirsten; Pasini, Alice; Baylin, Stephen; Easwaran, Hariharan
Abstract Background Bivalent chromatin refers to overlapping regions containing activating histone H3 Lys4 trimethylation (H3K4me3) and inactivating H3K27me3 marks. Existence of such bivalent marks on the same nucleosome has only recently been suggested. Previous genome-wide efforts to characterize bivalent chromatin have focused primarily on individual marks to define overlapping zones of bivalency rather than mapping positions of truly bivalent mononucleosomes. Results Here, we developed an efficacious sequential ChIP technique for examining global positioning of individual bivalent nucleosomes. Using next generation sequencing approaches we show that although individual H3K4me3 and H3K27me3 marks overlap in broad zones, bivalent nucleosomes are focally enriched in the vicinity of the transcription start site (TSS). These seem to occupy the H2A.Z nucleosome positions previously described as salt-labile nucleosomes, and are correlated with low gene expression. Although the enrichment profiles of bivalent nucleosomes show a clear dependency on CpG island content, they demonstrate a stark anti-correlation with methylation status. Conclusions We show that regional overlap of H3K4me3 and H3K27me3 chromatin tend to be upstream to the TSS, while bivalent nucleosomes with both marks are mainly promoter proximal near the TSS of CpG island-containing genes with poised/low expression. We discuss the implications of the focal enrichment of bivalent nucleosomes around the TSS on the poised chromatin state of promoters in stem cells.